Prevalence of mental disorders among prisoners in the state of Sao Paulo, Brazil. - Sergio Baxter Andreoli (Public Library of Science (PLoS), 2014)
Objective To determine the prevalence of psychiatric disorders in the prison population in the State of São Paulo, Brazil. Methods Through stratified random sampling, 1.192 men and 617 women prisoners were evaluated for the presence of psychiatric disorders by the Composite International Diagnostic Interview, 2.1 version, according to definitions and criteria of International Classification of Diseases (ICD-10). The prevalence estimates of mental disorders and their respective 95% confidence intervals were calculated and adjusted for sample design through complex sample analysis. Results Lifetime and 12-month prevalence rates differed between genders. Lifetime and 12-month prevalence of any mental disorder was, respectively, 68.9% and 39.2% among women, and 56.1% and 22.1% among men. Lifetime and 12-month prevalence of anxious-phobic disorders was, respectively, 50% and 27.7% among women and 35.3% and 13.6% among men, of affective disorders was 40% and 21% among women and 20.8% and 9.9% among men, and of drug-related disorders was 25.2% and 1.6% among women and 26.5% and 1.3% among men. For severe mental disorders (psychotic, bipolar disorders, and severe depression), the lifetime and 12-month prevalence rates were, respectively, 25.8% and 14.7% among women, and 12.3% and 6.3% among men. Conclusions This is the first large-scale epidemiological study performed with the prison population in Brazil, revealed high rates of psychiatric disorders among men and women. Many similarities, as well as some differences, were found between our results and those of studies conducted in other countries. The differences observed are more likely due to the peculiarities of the prison systems in each country than to the diagnostic criteria adopted in the studies. This fact reinforces the importance of conducting such studies as part of planning and development of appropriate policies for the particular mental health needs of specific prison populations.